PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN KEMANDIRIAN DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI KESEBANGUNAN DAN SIMETRI - Alfian Zaki, Ruli Nur (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
Interviews and observations showed low learning achievement of independence and fifth-grade students of SD Negeri 2 Tinggarjaya, so this research aims to improve the independence and student achievement in the subjects of Mathematics material congruency and symmetry. This research is the subject of a class action that takes fifth-grade students with a number of 30 students consisting of 12 men and 18 women. This study uses a model of Quantum Teaching is carried out2cycles, each cycle consisting of 2 meetings. Each cycle consists of planning, implementation, observation/observation, and reflection. Based on the result obtained in the first cycle, students' independence as much as79,58% with both criteria and the second cycles much as89,18%, thus increasing the criterion very well, while the acquisition of student achievement obtained in the first cycle the average value of the class of 58,67 with passing grade is achieved only 60%. in the second cycle, the acquisition of student achievement obtained an average value of 89,25class with mastery learning reaches 88,9%. The collection of data through questionnaires and student evaluation sheet, Quantum Teaching shows that the model can improve the independence and student achievement in the subjects of Mathematics material congruency and symmetry.